STRATEGI PENINGKATAN MINAT LITERASI ANAK BERBAHASA INGGRIS DI RUMAH SUSUN MARUNDA - Indra Gunara Rochyat; Ainur Rosyid; Adisti Ananda Yusuff (LPPM Universitas Nusa Mandiri, 2026)
This community service program was carried out in Neighborhood Rusunawa Marunda, with partners from economically non-productive community groups who participated in English language learning activities. Teaching and learning activities were carried out in a public space in the complex that did not have adequate supporting facilities. The main problems were divided into two aspects. Physical aspects included the lack of facilities for storing books and learning tools, thereby hampering the effectiveness of the learning process. Non-physical aspects include low interaction between teachers and students due to limited teaching staff. The PKM was implemented using participatory methods in activities, which included the provision of learning infrastructure and supporting learning. The solutions implemented included the provision of metal cabinets, bookshelves, new blackboards, and the addition of teaching staff through an interactive storytelling program. The program successfully created a conducive learning environment, improved communication skills, and strengthened collaboration between teachers and students. As a result, the target community was able to improve their literacy, knowledge, and skills. The application of appropriate solutions in physical and non-physical aspects demonstrates the importance of community-based learning facility innovations in improving the quality of education in public housing complexes. The concrete outcome of the PKM activity in the Marunda public complex is an impact that is not only short-term but also builds a foundation for literacy, language skills, and a sustainable participatory learning culture. The benefits directly felt by the participants encourage increased learning productivity and strengthen the role of partners as an educational ecosystem.